2021
DOI: 10.3389/fcell.2021.751490
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Ferroptosis-Related Long Non-coding RNA Prognostic Signature and Competing Endogenous RNA Network in Lung Adenocarcinoma

Abstract: Ferroptosis-related genes play an important role in the progression of lung adenocarcinoma (LUAD). However, the potential function of ferroptosis-related lncRNAs in LUAD has not been fully elucidated. Thus, to explore the potential role of ferroptosis-related lncRNAs in LUAD, the transcriptome RNA-seq data and corresponding clinical data of LUAD were downloaded from the TCGA dataset. Pearson correlation was used to mine ferroptosis-related lncRNAs. Differential expression and univariate Cox analysis were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Three ferroptosis-related lncRNAs (DUXAP8, LINC02609, and LUCAT1) ( Xing et al, 2021 ) were reported to significantly correlate with the overall survival and clinicopathological features of kidney renal clear cell carcinoma. In another study ( Fei et al, 2021 ), a ferroptosis-related lncRNA prognostic signature (FLPS), which included six ferroptosis-related lncRNAs, provided a new strategy for the prediction of prognosis in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Three ferroptosis-related lncRNAs (DUXAP8, LINC02609, and LUCAT1) ( Xing et al, 2021 ) were reported to significantly correlate with the overall survival and clinicopathological features of kidney renal clear cell carcinoma. In another study ( Fei et al, 2021 ), a ferroptosis-related lncRNA prognostic signature (FLPS), which included six ferroptosis-related lncRNAs, provided a new strategy for the prediction of prognosis in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that LUAD lncRNA plays an important role in prognosis and immunotherapeutic response. Several studies have developed lncRNA prognosis signatures, such as m6A-related ( Wang et al, 2021b ), ferroptosis-related ( Fei et al, 2021 ), pyroptosis-related ( Song et al, 2021 ), immune-related ( Qi et al, 2021 ), and metastasis-related lncRNA signatures ( Dou et al, 2021 ). However, NRLs are still being investigated, and their prognostic role in LUAD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al successfully constructed a novel ferroptosis-related lncRNAs signature, which may contribute to improve the prognosis prediction and immunotherapy response of non-small cell lung cancer (NSCLC) patients [20]. Fei et al identi ed the prognostic ferroptosis-related lncRNAs in lung adenocarcinoma (LUAD) and constructed a prognostic signature which provided a new strategy for the evaluation and prediction of prognosis in LUAD [21]. Xing et al identi ed three ferroptosis-related DELs (DUXAP8, LINC02609 and LUCAT1) which can be used as prognostic signatures to predict the outcome of patients with KIRC [22].…”
Section: Construction and Validation Of The Cerna Network Based On Th...mentioning
confidence: 99%